Pembinaan Menumbuhkan Semangat Budaya Literasi Santri : Studi Kasus di Pondok Pesantren Sirojut Tholibin Plosokandang Tulungagung - Nik Haryanti; Endah Siswati; Dhafa Andrian Saputra (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
This research departs from the phenomenon that occurred in Islamic boarding schools that are still not strong in developing a literacy culture in creating a generation that is waiting through educational leadership. The purpose of this research is to find out the literacy culture for students in the digital era, literacy facilitation for students and the impact of literacy culture for students at the Sirojut Tholibin Plosokandang Islamic boarding school. The methods used in this service activity are the lecture method, question and answer method, and discussion method. The cottage-based literacy movement is carried out in three stages, namely the habituation stage, the development stage, and the learning stage. The results of the implementation of service at Sirojut Tholibin Plosokandang related to literacy culture in this all-digital era can be held properly and smoothly in accordance with the work program that has been prepared. The purpose of this work program is so that Indonesian youth, especially students in Sirojut Tholibin Plosokandang, do not abandon the reading culture even though the times are increasingly sophisticated, especially in social media. Utilizing the technology they have for positive things for future provisions. Continue to develop a literate culture so that it can create a work that can be enjoyed by the general public. And the hope is that in the future when they become alumni students, they will be able to compete with the outside world. That is the hope of the community service implementation team and the caregivers of Sirojut Tholibin Plosokandang.